The marine compound and elongation factor 1A1 inhibitor, didemnin B, provides benefit in western diet-induced non-alcoholic fatty liver disease. (November 2020) - Wilson, Rachel B.; Chen, Yun Jin; Sutherland, Brian G.; Sawyez, Cynthia G.; Zhang, Richard; Woolnough, Taylor; Hetherington, Alexandra M.; Peters, Kia M.; Patel, Krisha; Kennelly, John P.; Leonard, Kelly-Ann; Schuurman, Meg; et al.
Graphical abstract: Highlights: Elongation factor 1A1 inhibitor didemnin B improves fatty liver, glucose tolerance, and blood lipids in obesity. Didemnin B moderately upregulates pathways involved in cell stress response and energy balance in the liver. Didemnin B targets cells involved in liver inflammation and fibrosis. Abstract: Inhibition of eukaryotic elongation factor 1A1 (EEF1A1) with the marine compound didemnin B decreases lipotoxic HepG2 cell death in vitro and improves early stage non-alcoholic fatty liver disease (NAFLD) in young genetically obese mice. However, the effects of didemnin B on NAFLD in a model of long-term diet-induced obesity are not known. We investigated the effects of didemnin B on NAFLD severity and metabolic parameters in western diet-induced obese mice, and on the cell types that contribute to liver inflammation and fibrosis in vitro. Male 129S6 mice were fed either standard chow or western diet for 26 weeks, followed by intervention with didemnin B (50 μg/kg) or vehicle by intraperitoneal (i.p.) injection once every 3 days for 14 days. Didemnin B decreased liver and plasma triglycerides, improved oral glucose tolerance, and decreased NAFLD severity. Moreover, didemnin B moderately increased hepatic expression of genes involved in ER stress response ( Perk, Chop ), and fatty acid oxidation ( Fgf21, Cpt1a ). In vitro, didemnin B decreased THP-1 monocyte proliferation, disrupted THP-1 monocyte-macrophage differentiation, decreased THP-1 macrophage IL-1β secretion, and decreased hepatic stellate cell (HSteC) proliferation and collagen secretion under both basal and lipotoxic (high fatty acid) conditions. Thus, didemnin B improves hepatic steatosis, glucose tolerance, and blood lipids in obesity, in association with moderate, possibly hormetic, upregulation of pathways involved in cell stress response and energy balance in the liver. Furthermore, it decreases the activity of the cell types implicated in liver inflammation and fibrosis in vitro . These findings highlight the therapeutic potential of partial protein synthesis inhibition in the treatment of NAFLD.